Characterizing thrombus adhesion strength on common cardiovascular device materials - Kannojiya, Vikas; Almasy, Sara E.; Monclova, Jose L.; Contreras, Jerry; Costanzo, Francesco; Manning, Keefe B. (Frontiers in Bioengineering and Biotechnology, 2024)
Thrombus formation in blood-contacting medical devices is a major concern in the medical device industry, limiting the clinical efficacy of these devices. Further, a locally formed clot within the device has the potential to detach from the surface, posing a risk of embolization. Clot embolization from blood-contacting cardiovascular devices can result in serious complications like acute ischemic stroke and myocardial infarction. Therefore, clot embolization associated with device-induced thrombosis can be life-threatening and requires an enhanced fundamental understanding of embolization characteristics to come up with advanced intervention strategies. Therefore, this work aims to investigate the adhesive characteristics of blood clots on common biocompatible materials used in various cardiovascular devices. This study focuses on characterizing the adhesion strength of blood clots on materials such as polytetrafluoroethylene (PTFE), polyurethane (PU), polyether ether ketone (PEEK), nitinol, and titanium, frequently used in medical devices. In addition, the effect of incubation time on clot adhesion is explored. Results from this work demonstrated strongest clot adhesion to titanium with 3 hours of incubation resulting in 1.06 ± 0.20 kPa detachment stresses. The clot adhesion strength on titanium was 51.5% higher than PEEK, 35.9% higher than PTFE, 63.1% higher than PU, and 35.4% higher than nitinol. Further, adhesion strength increases with incubation time for all materials. The percentage increase in detachment stress over incubation time (ranging from 30 minutes to 3 hours) for polymers ranged from at least 108.75% (PEEK), 140.74% (PU), to 151.61% (PTFE). Whereas, for metallic surfaces, the percentage rise ranged from 70.21% (nitinol) to 89.28% (titanium). Confocal fluorescence imaging of clot remnants on the material surfaces revealed a well-bounded platelet-fibrin network at the residual region, representing a comparatively higher adhesive region than the non-residual zone of the surface.